SIFAT HIPOGLISEMIK PAKAN TINGGI PROTEIN KEDELAI PADA MODEL DIABEIK INDUKSI ALLOXAN [Hypoglicemic Property of a High-Protein Soybean Based Feed in Model alloxan Induced Diabetic] - C. Retnaningsih; Zuheid Noor; Y. Marsono (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2001)
Hypoglicemic properties of soybean protein were evaluated in alloxan-induced diabetic rats. Twenty eight mature male Sprague Dawley (SD) rats (250-300g) were used and divided into four groups of seven rats. They were: 1) Placebo Standars (PS); 2) Alloxan Injection Standard (AS); 3) Alloxan injection soybean protein 250% (APK 250) dan 4) Alloxen injection soybean protein 100% (APK 100). One group was injected with aquabidest (Placebo) and three group were diabetic induced by alloxan injection (80 mg/kg of body weight by intramuscular injection).Placebo-Standard (PS) and Alloxan injection Standar (AS) groups were fed standard diet whereas APK 250 100 were fed soybean protein deit for 42 days. Concentration of serum glucose was determined before incention (0day) and 1, 2, 143, 21, 28, 35, and 42 days after injection.The result showed that alloxan injection increased the level of serum glucose. Bioassay experiment demonstrated that diet on high conceration of soybean protein (250%) decreased the level of serum glucose from 351,44 mg/dl to 230,62 mg/dl (34,37%) while soy protein 100% descreased the level of serum glucose.